Perbandingan User Interface Aplikasi Mobile Pemesanan Tiket Pesawat Online dengan Design Thinking - Anandhi Tristiaratri; Adam Hendra Brata; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Domestic flights are increasing from year to year impact on the increase of tickets. It is to develop mobile online applications. The examples are Traveloka, Tiket.com, and etc. From the many applications, users will feel the different user experience. It can be caused by interface or usability. This research will examine about interface and usability of android applications which can be used as a reference for building similar applications. The method that used in this reasearch is design thinking. To collect data there are several ways such as interviews and questionnaires. Based on the results of research, the user experience of Traveloka and Tiket.com obtain an average value of 5.8/7 and 5.3/7. That number proves that both applications have usefulness, easy of use and learn, and satisfication is good enough for the users.